Comparison of hemodynamic and analgesic effects of interscalene block with bupivacaine versus bupivacaine-dexmedetomidine combination for shoulder arthroscopy under general anesthesia - Mullick, Jahangir; Ray, Amit Kumar; Chakraborty, Soma; Bidyut Bikas Gharami, (Asian Journal of Medical Sciences, 2024)
Background: The interscalene block in shoulder arthroscopy is a well-established procedure. Many drugs have been used as adjuvants to local anesthetics to increase the quality of block in regional anesthesia, with variable results. Aims and Objectives: The present study was designed to evaluate the effect of dexmedetomidine as an adjuvant to bupivacaine during interscalene block in terms of intraoperative hemodynamic changes and postoperative analgesia. Materials and Methods: Thirty patients, aged 20–55 years of either sex, American Society of Anesthesiologists physical status I-II, scheduled for shoulder arthroscopic surgery for <2 h, were allocated into two equal groups to receive inj. bupivacaine (0.25%) with inj. dexmedetomidine 1 μg/kg (Group BD, n=15) or inj. bupivacaine (0.25%) with 1 mL normal saline (Group BS, n=15), total volume 20 mL in each case. After settlement of the interscalene block, both groups received general anesthesia as per standard protocol. Hemodynamic parameters (heart rate [HR] and systolic blood pressure [SBP]) were assessed in the intraoperative period, and postoperative pain was assessed using a visual analog scale score in the postoperative period at stipulated time points. Results: The mean values of HR and SBP were considerably low at all observed time points in the intraoperative period (i.e., at 10 min, 30 min, 60 min, 90 min, and120 min), in comparison with the saline group (P<0.0001). VAS scores between the two groups were considerably lower only at 8, 12, and 18 h in patients receiving dexmedetomidine (P<0.001). Conclusion: Dexmedetomidine as an adjuvant with bupivacaine can achieve a better hemodynamic profile (lower HR and SBP) in the intraoperative period. Also, the use of dexmedetomidine provides better postoperative analgesia profiles in the later part of the postoperative period (8–18 h), and the effect usually wanes by 24 h.